Aspects of Chinese phonotactics against a comparative background of Polish. Dubieties and prospects (A preliminary draft) - Bańczerowski, Jerzy (Scripta Neophilologica Posnaniensia, 2019)
Aspects of Chinese phonotactics against a comparative background of Polish. Dubieties and prospects (A preliminary draft)